Keadilan Poligami Perspektif Gender Studi Perubahan Sosial Dalam Kitab Nazhariyah AlMaqashid Karya Ibnu Asyur - Subur Wijaya (LP2M Universitas PTIQ Jakarta, 2016)
This article specifically deals with the polygamy in the view of Ibn Asyūr in his book: ”Nazhariyah al-Maqashid” which affirms male enrollment (husbands) to marry more than one wife with record capable and fair. Ibn Asyūr’s view in the writer’s view is the response of the three major streams of scholars’ opinion of polygamy, that is; 1) allowable flow, 2) flow that tightens the ability condition, and 3) prohibit flow. The authors themselves are more likely to agree with the second flow than others, given the laws governing marriage in Indonesia allowing polygamy with various conditions. If polygamy is done wisely, and meet the existing requirements, it will certainly strengthen the happy family building, mawaddah wa rahmah